(4-4x)(x-3)
4x-12-(4x^2)+12x
(-4x^2)+16x-12=(pxq)(x)
Answer:
The standard form of the quadratic equation is x² + 3·x - 4 = 0
Step-by-step explanation:
The standard form of a quadratic equation is a·x² + b·x + c = 0
Given that the expression of the quadratic equation is (x + 4)·(x - 1) = y, we can write the given expression in standard form by expanding, and equating the result to zero as follows;
(x + 4)·(x - 1) = x² - x + 4·x - 4 = x² + 3·x - 4 = 0
The standard form of the quadratic equation is x² + 3·x - 4 = 0
The graph of the equation created with MS Excel is attached
8 ft up the building is where the top of the ladder touches (use Pythagorean Theorem)
<span />
Answer:
6 men 6 women or 2 men 10 women
I THINK IT WOULD BE 54 INCHES TALL I THINK